Cubane-like Bismuth-iron cluster: synthesis, X-ray crystal structure and theoretical characterization of the [Bi4Fe8(CO)28]4- Anion - Monakhov, Kirill; Zessin, Thomas; Linti, Gerald W. (European journal of inorganic chemistry, 2010)
The reaction of cyclo-Bi4[Si(SiMe3)3]4 (1) with Na2[Fe(CO)4] in the presence of nBu4NCl leads to the formation of the cage compound [nBu4N]4[Bi4Fe8(CO)28] (2). According to X-ray single-crystal structure analysis, the faces of the tetrahedral Bi4 core are capped by Fe(CO)3 moieties in a μ3 fashion to give a cubanoid Bi4Fe4 framework. The four Fe(CO)4 fragments are μ1-coordinated to bismuth, each. With 12 skeletal electron pairs the [Bi4Fe8(CO)28]4- anion (2a) is a Bi4Fe4 cubane. The negative charge is localized within cluster 2a according to the NBO analysis of its derivatives. The strength of metal-ligand interactions Bi-μ3-Fe(CO)3 is responsible for the size of the cluster's cubic core. NICS computations at the cage centers of considered molecules show that 2a has paratropic character, whereas removal of four μ1-Fe(CO)4 fragments from latter causes spherical aromaticity of the modified clusters [Bi4Fe4(CO)12]4- (2aa) and [Bi4Fe4(CO)12]2+ (2ab), mediated by a Bi4 cluster π orbital.
Gesehen am 03.05.2023
Im Titel sind die Zahlen "4", "8" und "28" tiefgestellt, "4-" ist hochgestellt